Tension values to describe soil-water retention curve on Cerrado soils - Silva, Euzebio Medrado da; Lima, Jorge Enoch Furquim Werneck; Azevedo, Juscelino Antônio de; Rodrigues, Lineu Neiva (Pesquisa Agropecuaria Brasileira, 2006)
Soil-water retention curve is essential in studying soil-water relations. The choice of the number and the combination of the tension points for describing soil-water retention curve is usually done in an arbitrary manner. The objective of this work was to define the least number and the best combination of the necessary tension points to describe the adequate soil-water retention curve of Cerrado soils. Five soil-water retention curves from different soils were utilized and taken as a reference, each one described with 15 points, measured by the centrifuge method and fitted with Genuchten model. For each soil sample, 385 curves were generated with six, seven, eight, and nine points, in order to be compared with the reference curve. The statistical distribution analysis of the sum of the normalized square error between the generated curves and the respective reference curve allowed defining a probability model that was used as a tool for choosing the best combinations of the tension points. The combination defined by the eight tension values of 1, 3, 6, 10, 35, 84, 611 e 1.515 kPa is recommended for describing soil-water retention curve for Cerrado soils.